Analyzing local fashion communities/SME`s from Ethiopia and Ukraine and devising solutions for sustainable businesses. - Khuarana, Karan; Ryabchykova, Kateryna (Universitas Airlangga, 2017)
The ever-increasing share of fast fashion consumerism shadowed the profound craftsmanship of local produce in the developing countries. This subsequently created hardship to the local communities and designers across the non-western world which belongs to small and medium scale enterprise sector. Beyond this the fashion commodities saw a substantial fall in design elements which made the products very banal in nature. Consequently, the trade turned towards conscious consumption and here emerged a few sustainable designers and craft oriented communities which attracted attention in the recent past. Problems of sustainability and consumption are burning issues nowadays, fashion houses and international brands propagandize purchase for better consumer base, whereas originally sustainable local-based craftsmen still stay in the shade. Due to lack of expert management and target allocated branding real sources of national heritage cannot gain fame on the international level. In this research, we have studied and analyzed the problems faced by hereditary communities and ethnic designers which lie in small and medium scale enterprise sector from two developing economies Ethiopia and Ukraine. The main purpose of the work is to design effective marketing & management strategy for expansion of local communities and entrepreneurs to the international level. Particular attention is given to communities and designers who promote national heritage and for a part of small and medium scale enterprises which are one of the concerns of economic development of the two countries. Keywords: Fashion Communities, Small and Medium Scale Enterprise (SME), Fashion Marketing and Branding, Non-Western Economies, Sustainable Development.